Has the Russian invasion of Ukraine reinforced anti-globalization sentiment in Austria? - Jerg Gutmann; Hans Pitlik; Andrea Fronaschütz (Empirica, 2023)
The Russian invasion of Ukraine has caused disruptions in international trade and highlighted the dependency of small open economies in Europe on imports, especially of energy. These events may have changed Europeans' attitude towards globalization. We study two waves of representative population surveys conducted in Austria, one right before the Russian invasion and the other two months later. Our unique dataset allows us to assess changes in the Austrian public's attitudes towards globalization and import dependency as a short-term reaction to economic turbulences and geopolitical upheaval at the onset of war in Europe. We show that two months after the invasion, anti-globalization sentiment in general has not spread, but that people have become more concerned about strategic external dependencies, especially in energy imports, suggesting that citizens' attitudes regarding globalization are differentiated.
Keywords: F13; F51; F52; N40; 330; Austria; Crisis; Conflict; Globalization attitudes; Russian invasion; War